ANALISIS KECACATAN KEMASAN PRODUK OKKY JELLY DRINK PERISA BLACKCURRANT SEBAGAI UPAYA PERBAIKAN KUALITAS DENGAN METODE DMAIC PADA PT. TRITEGUH MANUNGGAL SEJATI - Suharto Suharto (Fakultas Teknik Universitas Tulang Bawang Lampung, 2019)
This study aims to determine and identify the causes of defects in the production process of PT. Triteguh Manunggal Sejati and know the level of sigma level. This research uses the six sigma method with the DMAIC approach as a quality control tool, which includes the Define, Measure, Analyze, Improve and Control stages. Based on this study the results obtained are the level of sigma level at PT.Triteguh Manunggal Sejati is 4.96, which means that in the stage of sigma level the company has not reached the level of six sigma levels because in the production process at PT.Triteguh Manunggal Sejati still has product defects in the production process not yet achieved zero defect. The causes of product defects are based on cause and effect diagrams namely lid / seal defects are leaky lid, broken lid, and tilted lid. Kata kunci : Defect, Six Sigma, DMAIC, cause and effect diagram